2023
DOI: 10.1021/acsomega.2c07625
|View full text |Cite
|
Sign up to set email alerts
|

Thiocarbohydrazone and Chalcone-Derived 3,4-Dihydropyrimidinethione as Lipid Peroxidation and Soybean Lipoxygenase Inhibitors

Abstract: The potential of the 4,6-diphenyl-3,4-dihydropyrimidine-2­(1H)-thione (abbreviated as KKII5) and (E)-N′-benzylidene­hydrazine­carbothiohydrazide (abbreviated as DKI5) compounds as possible drug leads is investigated. KKII5 and DKI5 are synthesized in high yield of up to 97%. Their structure, binding in the active site of the LOX-1 enzyme, and their toxicity are studied via joint experimental and computational methodologies. Specifically, the structure assignment and conformational analysis were achieved by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Finally, as a continuation of our previous studies, where similar molecules presented strong binding affinity in macromolecules [ 10 , 11 ], the present compounds were tested through in silico molecular docking in different macromolecules to check if the present compounds are suitable for specific biological targets. The results gave promising bindings and SwissADME showed that both compounds obey Lipinski’s Rule of Five.…”
Section: Introductionmentioning
confidence: 96%
“…Finally, as a continuation of our previous studies, where similar molecules presented strong binding affinity in macromolecules [ 10 , 11 ], the present compounds were tested through in silico molecular docking in different macromolecules to check if the present compounds are suitable for specific biological targets. The results gave promising bindings and SwissADME showed that both compounds obey Lipinski’s Rule of Five.…”
Section: Introductionmentioning
confidence: 96%
“…This procedure is very important for computational drug design. Some potential biological compounds fail to reach clinical trials due to their unfavorable (ADME) parameters [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%